Analisis Laju Infiltrasi Pada Tutupan Lahan Perkebunan Dan Hutan Tanam Industri (HTI) Di Daerah Aliran Sungai (DAS) Siak - David, Muhammad; Fauzi, Manyuk; Sandhyavitri, Ari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The change in land use may affect the availability of ground due the change of infiltration in to the soil. One of the significant factors that can increase infiltration rate is vegetation coverage. The purpose of this study is: (1) to determine the infiltration rate of 4 type of vegetation land cover and (2) to determine the land cover classification based on the average value of the infiltration capacity. The research was conducted in 4 different land cover : immature palm oil plantation, mature palm oil plantation, rubber plantation and acacia Industrial plantation forest. Infiltration test for each land cover was processed at 8 points on 4 soil types and the obtained data was processed using Horton infiltration method. Based on analysis resulting using Horton infiltration method, immature palm oil plantation with 0,54 cm/hour of infiltration capacity is classified as group B (medium surface flow), oil palm plantation with 0,18 cm/hour of infiltration capacity as group C (between high and medium surface flow), rubber plantation with 0,92 cm/hour of infiltration capacity as group A (low surface flow), and acacia plantation area with 0,91 cm/hour of infiltration capacity as group A (low surface flow). Based on the regression result between the actual infiltration rate and Horton infiltration acquired a very real relation, so that Horton infiltration method can be used to estimate infiltration rate of four types of land cover in Siak Watershed.Key words: Change in land use, Double ring infiltrometer, Horton infiltration method, Infiltration rate.